Analisis Kendala dan Peluang Pengembangan UMKM di Era Ekonomi Digital - Terry Sugihardi (Program Studi Manajemen Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2026)
This study aims to analyze the challenges and opportunities for the development of Micro, Small, and Medium Enterprises (MSMEs) in the digital economy era. MSMEs play a strategic role in Indonesia's economy, but digital transformation has not been evenly implemented because of limited digital literacy, managerial capability, access to finance, infrastructure quality, business legality, transaction security, and dependency on digital platforms. This study applies a descriptive qualitative approach using a literature review method. Data were collected from official government publications, digital economy reports, and relevant academic literature. The analysis was conducted through data reduction, issue categorization, the development of challenge and opportunity matrices, and interpretive conclusion drawing. The findings indicate that the main obstacles faced by MSMEs are not only related to access to digital devices, but also to the ability to use technology for marketing, financial management, customer service, product innovation, and business decision-making. On the other hand, development opportunities are increasingly available through marketplaces, social media, digital payments, logistics services, technology-based financing, content-based marketing, and consumer data utilization. This study concludes that MSME development in the digital economy requires the integration of internal capacity building, continuous mentoring, consumer protection, access to finance, and an inclusive digital ecosystem.